Participation in rural development – the view of non-participants - Kim Pollermann (Regional Studies Association; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2019)
To address the challenges in rural areas the support for rural development with participatory approaches has a long tradition in EU funding programmes. One corresponding instrument is LEADER, which is a place-based, participatory approach to bring together public, private and civil society organisations. Within LEADER the different stakeholders come together in a Local Action Group (LAG) as a type of a public-private partnership. Those groups collaborate on the basis of an integrated local development strategy (LDS) and administer own budgets to support projects. Although there are usually broad participation opportunities, some observations in literature mention problems like that only the "usual suspects" (age over 40, higher education, male) get involved in such participations. It is a well established instrument to ask the participants of such processes about their view of the cooperation within their LEADER decision making body to examine their satisfaction with decision making procedures or their estimations about the output quality. But for some research questions an external view would be more appropriate. Thus, this contribution brings into focus the estimations of non-participants to examine their opinions about possibilities for participation or the legitimacy of decision-making within LEADER-processes. To collect this information an online-survey is used. Therefore, in eight LEADER-Regions about 50-100 non-participants (per region) got e-mail invitations for this survey in four different federal states in Germany. The "non-participants" were defined as persons who are neither members of the decision making body nor beneficiaries of the LEADER-projects. Respondents come from municipalities as well as from different associations of the civil society. This presentation contains preliminary results concerning the external views of the work of LEADER to gain insights about the possibilities of participation and possible obstacles to participate.
Conference: RSA Annual Conference 2019: Pushing Regions beyond their Borders, 5th - 7th June 2019, University of Santiago de Compostela, Spain
Keywords: R58; 330; LEADER; participation; rural development